Pendampingan Pembukuan Sederhana Untuk Pedagang Pasar Tradisional - Mulyawan; Khaerul Anam; Abdul Muhyi; Achmad Fajar (CV. Multi Kreasi Media, 2023)
Traditional market vendors play a vital role in supporting local economies and contribute significantly to community economic activities. However, most of them have not implemented proper bookkeeping systems, resulting in difficulties in managing cash flow, calculating profits, and accessing formal financial services. This program aims to provide simple bookkeeping assistance to traditional market traders to help them gain basic financial record-keeping skills. The program involved initial observation, development of a simple bookkeeping module, in-person training sessions, and hands-on assistance in daily financial recording. The bookkeeping system was tailored to the needs of small-scale businesses, covering records of income, expenses, and profit-loss, using notebooks and easy-to-understand paper forms. The results indicated an increased awareness among traders about the importance of financial documentation and their ability to independently create basic financial reports. Additionally, some vendors expressed interest in saving and accessing banking services as part of improved financial management. This initiative had a positive impact on enhancing the financial literacy of traditional traders and encouraged the development of a more organized business administration culture. In the future, such mentoring programs are expected to continue periodically and evolve toward the digitalization of simple bookkeeping systems via mobile applications.